An Analytical Study of Mergers and Acquisitions of Banking Sector in India - Gupta , Sunil; Singh, Gurbaksh (Gyan Management Journal, 2015)
Indian Banking System for the last two centuries has seen many developments. Merger is the combination of two or more companies which can be merged together either by way of amalgamation or absorption. Indian banking perspective to change in the financial market!>
Keywords: Capital Adequacy; Assets; Management; Earning; Liquidity; Solvency and Ratio